1998
DOI: 10.1021/ic980791u
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Palladium(II) and Platinum(II) Complexes of Bis(dimethylamino)porphyrazine

Abstract: The unsymmetrical porphyrazine (tetraazaporphyrin) bearing a single peripheral bis(dimethylamino) functionality, Mg[pz(NMe(2))(2)(Pr)(6)], was prepared by base-catalyzed cross condensation of dipropyl maleonitrile (in excess) with dimethylamino maleonitrile. The freebase (2H[pz(NMe(2))(2)(Pr)(6)]) and centrally metalated forms (M[pz(NMe(2))(2)(Pr)(6)]; M = Ni(II), Cu(II), Mn(III)) were prepared by treatment of Mg[pz(NMe(2))(2)(Pr)(6)] with trifluoroacetic acid and then the appropriate metal salt. PdCl(2) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 28 publications
5
69
0
Order By: Relevance
“…13 Thus, as an extension of this work, the synthesis of the more intriguing unsymmetrical 3:1 pzs bearing a single polyether amino-substituted pyrrole ring was undertaken. Due to the compatible rates of cyclization of dipropylmaleonitrile 6 and various aminomaleonitriles, 5 as the second agent for the crossed Linstead macrocyclizations. Dinitrile 4 has been previously synthesized, 15 while iodide 3 was obtained from commercially available tetra(ethylene)glycol 1 by mono-protection and conversion to the corresponding iodide 3.…”
Section: Synthesis Of Polyether-appended Aminoporphyrazinesmentioning
confidence: 99%
“…13 Thus, as an extension of this work, the synthesis of the more intriguing unsymmetrical 3:1 pzs bearing a single polyether amino-substituted pyrrole ring was undertaken. Due to the compatible rates of cyclization of dipropylmaleonitrile 6 and various aminomaleonitriles, 5 as the second agent for the crossed Linstead macrocyclizations. Dinitrile 4 has been previously synthesized, 15 while iodide 3 was obtained from commercially available tetra(ethylene)glycol 1 by mono-protection and conversion to the corresponding iodide 3.…”
Section: Synthesis Of Polyether-appended Aminoporphyrazinesmentioning
confidence: 99%
“…1a). [35][36][37] UV-Vis spectra were recorded on a Hitachi U-1900 spectrophotometer. UV-Vis monitored titrations were carried out in methanol- 38 The C hydrogen atoms were included in calculated positions with C-H = 0.93 -0.98 Å and refined as riding on their corresponding carbon atoms, with Uiso (H) = 1.2 Ueq (C) or 1.5 Ueq (methyl C).…”
Section: Methodsmentioning
confidence: 99%
“…[268][269][270][271][272][273][274][275] For instance, asymmetric A 3 B type phthalocyanine analogues can easily form mono-or dinuclear phthalocyanine analogues 92-95 when reacted with the main-group or transition-metal ions ( Figure 6). Similarly, Ercolani and co-workers have shown that six out of eight available pyridine-type nitrogen atoms in symmetric phthalocyanine could be methylated using standard methylation agents.…”
Section: Peripheral Substituent Coordination Approachmentioning
confidence: 99%